Remission of chronic spontaneous urticaria following omalizumab with gradually extended dosing intervals: Real-life data - SALMAN, ANDAÇ; AKTAŞ, MERYEM (WILEY, 2021)
Omalizumab is a well-established treatment option in chronic spontaneous urticaria unresponsive to antihistamines at standard or higher doses. However, characteristics of the remission and relapse following the withdrawal of omalizumab remain largely unknown. We aimed to define the characteristics of remission in CSU following omalizumab with gradually lengthened dosing intervals in this retrospective study of 102 patients who were treated with at least 5 doses of omalizumab between 2015 and 2020. Of 102 patients, 70 (68.6%) showed a CR to omalizumab at standard doses. Omalizumab could be discontinued in 47 of 70 patients using gradually lengthened dosing intervals. Following a mean follow-up duration of 12.2 months, 25 (58.1%) patients were still in remission while 18 (41.9%) had relapse (Follow-up data were not available in 4 patients). The relapses were unresponsive to antihistamines in 14 patients (77.7%), however, retreatment with omalizumab led to complete control of symptoms. The patients younger than 40 were more likely to relapse. Despite the need for comparison with fixed-dosing intervals in larger, prospective studies, the results of this study imply that omalizumab with gradually extended dosing intervals might provide a long duration of remission in CSU.
Keywords: chronic spontaneous urticarial; omalizumab; recurrence; remission